Long term effect of infection control practices and associated factors during a major Clostridium difficile outbreak in Costa Rica - Roy A Wong-McClure; Elenita Ramírez-Salas; Nury Mora-Brenes; Lorena Aguero-Sandí; Maritza Morera-Sigler; Xiomara Badilla-Vargas; Marcela Hernández-de Merzerville; Michele O’Shea; Elizabeth Bryce (Journal of Infection in Developing Countries)
Introduction: The C. difficile BI/NAP 1 hyper virulent strain has been responsible for the nosocomial outbreaks in several countries. The present study describes the infection control strategies utilized to achieve outbreak control as well as the factors associated with a C. difficile BI/NAP 1 hyper virulent strain outbreak in Costa Rica. Methodology: A descriptive analysis of the C. difficile outbreak was completed for the period of January 2007 to December 2010 in one affected hospital. An unmatched case-control study was subsequently performed to evaluate the association of exposure factors with C. difficile infection. Results: The pattern of the outbreak was characterized by a sharp increase in the incidence rate during the initial weeks of the outbreak, which was followed by a reduction in the incidence curve as several infection control measures were implemented. The C. difficile BI/NAP1 infection was associated with the prescription of antibiotics, in particular levofloxacin (OR: 9.3; 95%CI: 2.1-40.2), meropenem (OR: 4.9, 95%CI: 1.0-22.9), cefotaxime (OR: 4.3, 95%CI: 2.4-7.7), as well as a medical history of diabetes mellitus (OR: 2.9, 95%CI: 1.5-5.8). Conclusions: The infection control strategies implemented proved to be effective in achieving outbreak control and in maintaining the baseline C. difficile incidence rate following it. The reported C. difficile outbreak was associated with the prescription of broad-spectrum antibiotics and a medical history of diabetes.